THE IMPORTANT ROLE OF LACTATING CORNER AT PKU MUHAMMADIYAH YOGYAKARTA, INDONESIA - Marwati, Triyani (Universitas Ahmad Dahlan, 2014)
Background:Breastfeeding offers special health benefits to both infant and mother. A breastfeeding-friendly hospital might be an essential factor for predicting breastfeeding rates among women.Method: explored the impact of breastfeeding-friendly support on the intention of mothers to continue breastfeeding, we conducted a survey to the women who visited in Muhammadiyah Hospital of Yogyakarta.Result: The findings of the present study suggested that to encourage and increase the rate of continued breastfeeding 90% respondent understands the important of lactating corner. The respondent stated lactating corner provided good breastfeeding education to the women.Conclusion: Hospital should establish dedicated breastfeeding rooms and maintain a comfortable and clean environment. Keywords: exclusive breast milk, counseling on health promotion,lactation corner